2017
DOI: 10.1021/acs.jafc.7b00670
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Study of Silver Nanoparticles in Poultry Production

Abstract: Silver nanoparticles (AgNPs) are of interest due to their antimicrobial activity and are seen as potential candidates to replace antibiotics in animal husbandry. A few studies have focused on this new application, but they lack any considerations about residual accumulation of AgNPs in edible animal tissues and animal products. In this research, a 22 day in vivo study was carried out by oral administration of 20 nm spherical PVP coated AgNPs to hens. Six doses of approximately 1 mg kg of AgNPs-PVP each were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 37 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Alkaline solubilization, most commonly used with tetramethylammonium hydroxide (TMAH), was, on the other hand, found to be effective for releasing NPs from the tissues of Daphnia magna and Lumbriculus variegatus (AgNPs, AuNPs), 21 tissue and feces of rats (AgNPs, AuNPs), 19,22 ground beef (AgNPs, AuNPs), 21 human hepatoma (HepG2) cells (AgNPs) 13 and primary human endothelial cells (AuNPs). In a similar way, enzymatic treatment with the use of proteases has been applied for extracting NPs from the tissues of rats (AgNPs, AuNPs), 22,24 earthworms (AgNPs), 25 chicken meat (AgNPs), [26][27][28][29] game meat (Pb), 30 eff yolk (AgNPs) 31 and human synovial fluid (Cr, Co). 32 Macerozyme R-10, a mixture of pectinase, cellulase and hemicellulase, has been applied for NPs in plants, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline solubilization, most commonly used with tetramethylammonium hydroxide (TMAH), was, on the other hand, found to be effective for releasing NPs from the tissues of Daphnia magna and Lumbriculus variegatus (AgNPs, AuNPs), 21 tissue and feces of rats (AgNPs, AuNPs), 19,22 ground beef (AgNPs, AuNPs), 21 human hepatoma (HepG2) cells (AgNPs) 13 and primary human endothelial cells (AuNPs). In a similar way, enzymatic treatment with the use of proteases has been applied for extracting NPs from the tissues of rats (AgNPs, AuNPs), 22,24 earthworms (AgNPs), 25 chicken meat (AgNPs), [26][27][28][29] game meat (Pb), 30 eff yolk (AgNPs) 31 and human synovial fluid (Cr, Co). 32 Macerozyme R-10, a mixture of pectinase, cellulase and hemicellulase, has been applied for NPs in plants, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, in one study, oral administration of six doses of approximately 1 mg/kg of Ag NPs (diameter, 20 nm) did not leave any residues in the muscles of hens but only accumulated in the liver and eggs. 55 Kulak et al 43 found that oral administration of Ag NPs in broiler chickens resulted in residues in the small intestine and liver but not in the heart or breast muscle. It is considered that up to 100 µg Ag/L in drinking water is safe for human consumption without inducing adverse effects.…”
mentioning
confidence: 99%
“…Numerous studies have reported the sulfidation of Ag in various media, including animal, microorganism, plant, and diverse environmental matrices . Colloidal Ag may undergo a series of biotransformation, associated with the behavior of colloidal Ag in organisms, such as corona formation, biomolecule attachment, and interactions with cells. Silver is prone to integrating with S in organisms due to its strong binding force and the abundance of S in organisms.…”
Section: Resultsmentioning
confidence: 99%